Dzikir Bersama Lansia sebagai Upaya Menurunkan Gejala Psikosematis dan Bakti Sosial di Desa Cikampek Timur - Eneng Siti, Eneng Siti Julaeha; Megawati, Irma (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
This study focused on the importance of dzikir to reduce psychosematic symptoms that occur in the elderly in RT 03/09, East Cikampek Village, Karawang Regency. This study uses a qualitative field research method (field research) with a descriptive approach. Qualitative methods are used as a goal to be able to answer the problems that occur in the elderly in RT 03/09 East Cikampek Village. One indicator that can be measured from dzikir activities with the elderly is that it can be seen from changes in the behavior of the elderly who have carried out joint dhikr activities, this can be seen in some of the elderly who are starting to consistently participate in spiritual activities held at the local assembly.